An Aesthetics of Resistance: Voluspa Jarpa’s Necroarchivos (Periphērica, 2024)
Voluspa Jarpa’s installation Judd Shaft (2016–present) exposes declassified documents from the CIA to create what I term “necroarchivos.” Defined as contemporary artworks that highlight information previously lost, hidden, or manipulated, the necroarchivos resist “necropolitics,” or what Achille Mbembe defines as a politics of life and death; to present fragmented narratives, question official rhetoric, and (re)create histories, while advocating for collective memories. Under this conceptual framework, the artwork not only reveals violence but condemns aggressions against bodies and challenges their expendability. Against the current proliferation of authoritarianism and dictatorial regimes, art plays a critical role in alerting viewers of the tragic consequences of repressive governments. The artwork becomes a departure point to challenging the political and social sphere, create consciousness, and incite civic engagement. By conducting direct object study, interviewing the artist, and incorporating an interdisciplinary methodology, I map Jarpa’s aesthetics of resistance and her dialogue with archival art and a constellation of artworks to present the (in)accessibility of information and contest myriad disciplinary fields including history, politics, and art itself. I argue Jarpa’s necroarchivos comment on the (in)visibility of diverse power structures and their secrecy, “la imposibilidad de la lectura,” to register a counter history and contest the violence of the state apparatus.
Keywords: Voluspa Jarpa; Ivan Navarro; Patricio Vogel; Necroarchivos; Necropolitics; Dan Flavin; Donald Judd